Fulfillment of Women's Rights After Divorce: Dynamics and Transformation in the Legal Journey - Fadil, Fadil; Mazidah, Zidna; Mahmudi, Zaenul (De Jure: Jurnal Hukum dan Syari'ah, 2024)
The Supreme Court has ruled that in contested divorce cases, women are entitled to receive nafkah iddah, mut'ah, and nafkah madhiyah, provided they do not act nusyuz. However, this provision is not being effectively implemented. This study examines the fulfilment of women's rights post-contested divorce in the Malang Regency Religious Court. The goal is to identify shortcomings in implementing these regulations and propose solutions for more effective enforcement. The research employs an empirical-juridical method, using secondary data from interviews and documentation with key personnel at the Malang District Religious Court. The qualitative analysis refers to Soekanto's theory. The Findings indicate that the fulfilment of women's rights in contested divorces at the Malang Regency Religious Court is ineffective. The law is clear and understandable, and officers, judges, and staff are accountable. Furthermore, the Malang District Religious Court provides sufficient infrastructure and support. However, the unmet factors—community awareness and cultural attitudes—pose significant barriers. Low legal awareness and compliance, coupled with cultural tendencies in Malang District to avoid legal processes and seek quick resolutions, hinder effective implementation. Addressing these issues is crucial for the regulations to achieve their intended impact on women's rights post-divorce.